Mister vege and miss fruitty - Ahmad Fauzi, Nursyazwani; Ibrahim, Nor Azlinda; Jalil, Nur Amira; Zainuddin, Nurul Farhanah; Selamat, Nordibradini (Universiti Teknologi MARA, Kedah, 2018)
Mister Vege and Miss Fruitty are created to encourage children to eat more vegetables and fruits at the same time, it is to make the children to recognize the fruits and vegetable look and its name. This book will attract the children as the information in it is fun learning exercise for them to learn. This book is created to make the children recognized the fruits and vegetable at the same time, it could attract the children to eat more fruit and vegetable. Novelty and Uniqueness: Have variety of styles for the children to learn and understand the vegetable and fruit.